2018
DOI: 10.1111/jan.13804
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of undertaking fertility‐related discussions with teenagers and young adults with cancer: An interpretive phenomenological analysis

Abstract: Ongoing education and support for nurses may ensure teenage and young adult cancer patients' reproductive needs are met. Nurses need to consider ways to ensure female patients benefit from improved information regarding infertility risks and preservation options to support their reproductive needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Lack of enough information on oncofertility resources also could also lead to poor quality discussions of fertility issues. This result is consistent with previous studies, which indicate discomfort with recommending women to stop necessary cancer treatments to undergo fertility preservation therapy (Rosenberg et al., 2017; Wright et al., 2018). Other barriers to discussions that included concerns about exacerbating negative emotions and the decision‐making capacity of young patients were also the factors that have an impact on nurses’ attitudes toward oncofertility (Nobel Murray et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Lack of enough information on oncofertility resources also could also lead to poor quality discussions of fertility issues. This result is consistent with previous studies, which indicate discomfort with recommending women to stop necessary cancer treatments to undergo fertility preservation therapy (Rosenberg et al., 2017; Wright et al., 2018). Other barriers to discussions that included concerns about exacerbating negative emotions and the decision‐making capacity of young patients were also the factors that have an impact on nurses’ attitudes toward oncofertility (Nobel Murray et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, nurses who do not participate in the discussion may not understand the needs of AYA with cancer. Studies have demonstrated several challenges, including a lack of knowledge resulting in the avoidance of discussing fertility issues [ 15 ] and few opportunities for discussing fertility preservation immediately after diagnosis [ 16 ]. Moreover, a previous report has shown that nurses were concerned about exacerbating negative emotions and the decision-making capacity of young patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to cancer treatment, women may be susceptible to reduced fertility. Moreover, some women lose ovarian function temporarily, and others lose it permanently (Wright et al, 2018). Treatment of cancer usually causes longstanding fertility complications, the statistical values with estimated that about thirty to seventy-five percentage of male cancer patients and forty to eighty percent of female patients becoming infertile due to the effect of chemotherapy and radiotherapy (Miok et al, 2019).…”
Section: Introductionmentioning
confidence: 99%